Review of software process improvements - Casaverde Carpio, Diego Grell (2022)
Over time, different process improvement models have emerged to assess software quality and apply improvements based on the evaluation. Among the most outstanding are CMMI and ISO/IEC 15504, and MPS are the three main models for evaluating and improving software processes. The differences that are addressed in the article are benefits and maturity levels. CMMI is based on the ideas of evil reproduced in a framework with five levels. ISO/IEC 15504, formerly known as SPICE. It has a framework of 6 groups of maturity. MPS-BR is based on CMMI with the difference that it has seven maturity levels. The main difference between CMMI, MPS-BR, and ISO 15504 is their orientation. While CMMI is aimed at large companies, MPS-BR focuses on medium and small companies, and ISO 15004 is aimed at any company, whether large companies or PyMEs.